TUJUH TEORI ETIKA TENTANG TUJUAN HUKUM - Yong Ohoitimur (Studia Philosophica et Theologica, 2001)
By the term "law" I mean system of law that exists in a political territory. Every system of law consists in some necessary elements such as basic laws or constitutions promulgated by the legislative, regulations made by the judicative, practical decrees announced by the executive. The article shall delvein the topic of ethical theory concerning the purpose of law. Why questioning ethically the purpose of law? By questioning it I try to draw what the ethical reasons of promulgating laws would be in political society. Consequently, every law should not be put into practice in a society, unless it is corresponding with that certain ethical reasons. In so doing, I shall survey the ideas of the seven political philosophers: Hobbes, Cicero, Locke, Aquinas, Bentham, Kant, dan Salmond. From this general survey, I discover that every theory has its own ethical reason which is in line with its anthropology and political philosophy. Besides, every theory finds necessary ethics in its own contemporary context. However, as Indonesia is struggling with law enforcement, it would be helpful to learnfrom their ethical theory of purpose of law.